Metal‐Free Cyclization of ortho‐Nitroaryl Ynamides and Ynamines towards Spiropseudoindoxyls. (16th April 2018) - Marien, Niels; Reddy, B. Narendraprasad; De Vleeschouwer, Freija; Goderis, Steven; Van Hecke, Kristof; Verniest, Guido
Abstract: An efficient metal‐free cascade reaction between 1‐dibromovinyl‐2‐nitro‐substituted arenes and secondary amines results in the formation of polycyclic pseudoindoxyls in a single step. The reaction mechanism leading to these fused ring systems was investigated, and is believed to involve the initial formation of nitroarylated ynamines/ynamides. These intermediates cycloisomerize towards N‐alkenyl‐tethered 2‐aminoisatogens via a carbene intermediate as demonstrated by QTAIM (quantum theory of atoms in molecules) and ELF (electron localization function) analysis. A subsequent intramolecular dipolar cycloaddition afforded the title compounds.